Protected but not from Contamination: Antimicrobial Resistance Profiles of Bacteria from Birds in a Ghanaian Forest Protected Area - Sawyerr Louisa Modupe; Ntiamoa-Baidu Yaa; Owusu Erasmus Henaku; Kenji Ohya; Suzuki Masato; Odoi Justice Opare; Kayang Boniface Baboreka (Environmental Health Insights, 2021)
Resistance to antimicrobial agents is a growing concern in public health. It has been reported in wildlife from several places in the world though wild animals are not normally exposed to clinically used antimicrobial agents. Despite this, very little research has been done in Ghana to determine antimicrobial resistance in wild animals, particularly those in protected areas. In this study, the presence of colistin resistant and multidrug resistant (MDR) gram-negative bacteria in cloacal swabs of wild birds captured in a Ghanaian forest protected area were evaluated. A total of 195 isolates from 138 individual birds were obtained, identified and tested for resistance to colistin. The colistin-resistant isolates were subsequently tested for multidrug resistance to 4 other antimicrobial agents (Oxytetracycline, Streptomycin, Ampicillin and Ciprofloxacin). Colistin resistance was observed in 6.5% (9/138) of the birds and this was seen in only birds that were sampled close to the reception area of the protected area. About 50% of the colistin-resistant isolates were multidrug resistant. AMR isolates were obtained from birds that have been documented to show an insectivorous or omnivorous feeding preference. Data obtained from the study suggests that AMR and MDR occurred in wild birds from the Conservation Area and supports the claim that proximity to human impacted habitats (settlements/farmlands) increased the likelihood of carriage of AMR. Though the routes of transmission remain unclear, there is potential for spread from the wild birds to other wild/domestic animals and possibly back to humans.